ANALISIS KEMAMPUAN PENYELESAIAIN KONFLIK SISWA LAKI-LAKI DAN PEREMPUAN KELAS III SMP NEGERI 1 SIMPANG KANAN KABUPATEN ROKAN HILIR TAHUN PELAJARAN 2013/2014 - Tanson '; Raja Arlizoni Raja Arlizoni; Abu Asyar Abu Asyar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstracThis study aims to describe the ability to resolve conflicts and male students to describe the ability to resolve conflict female students. Assumptions formulated in this study are: Ability boys and girls in SMP Negeri 1 Simpang Kanan Rokan Hilir have different capacities to resolve conflicts. Measured students' capacity to resolve conflict and identified the indicators. Each student is experiencing conflict in their lives. Were used in this study population were male students and female students in Class III SMP Negeri 1 Simpang Kanan Rokan Hilir in the school year 2013/2014 a total of 77 students. If the members of the population or the subject (population) of less than 100, then it is better taken all that research is a study population or technique commonly referred to as saturated samples (total sampling). Thus the number of samples equal to the number of studies with mengambilsiswa both men (33) and women (44) as many as 77 students. Based on the results of data processing and analysis that has been done, it could be concluded (1) From the discussion, it was found that the ability to resolve conflicts benchmark boys Class III SMP Negeri 1 Simpang Kanan Rokan Hilir 2013/2014 academic year is higher than the female students. Highest percentage of capacity to resolve conflict male students obtained on aspects colaboration (61%) and accomodating (67%). (2) From the discussion, it was found that the ability to resolve conflicts benchmark Class III female students of SMP Negeri 1 Simpang Kanan Rokan Hilir highest academic year 2013/2014 in accommodating (39%)and imposing  aspect (27%). Keywords: Ability, Students, Conflict